Analisis Besaran Hidrograf Satuan Berdasarkan Karakteristik Daerah Aliran Sungai Siak (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Siak basin which is flowing through Pekanbaru has eleven sub basins. There are five sub basins in the north and six in the south of siak basin with each different characteristic.Completeness of the information sub basin characteristic data was very limited, thus it required an assessment about the parameter of basin characteristics. The assessment of thesecharacteristics used DEM data and the technology of Geographic Information System (GIS) to determine riverâs network. This basin characteristic data was used to determine the flood discharge using three synthetic unit hydrograph methods, there were Gama I, SCS (Soil conservation service), and ITB method. The synthetic unit hydrograph method that could be applied to each sub basin was found based on the principle of unit hydrograph with one millimetre of direct run off and volume error less than 5 %. Based on the result of case study on Siak sub basins, the synthetic unit hydrograph method that can be applied to each subbasin is ITB method, which the result of direct runoff (DRo) obtained 1 mm and volume error 0%.Keywords: Basin Characteristic, GIS, Synthetic Unit Hydrograph